Ecosystem services provided by urban ponds and green spaces: a detailed study of a semi-natural site with global importance for research. Issue 1 (16th March 2022) - Krivtsov, Vladimir; Forbes, Heather; Birkinshaw, Steve; Olive, Valerie; Chamberlain, David; Buckman, Jim; Yahr, Rebecca; Arthur, Scott; Christie, Derek; Monteiro, Yamina; Diekonigin, Cameron
Abstract: Ponds and the adjacent green spaces are an important part of urban blue-green Infrastructure (BGI) and contribute to a number of ecosystem services, including alleviation of flood risk, amelioration of climatic fluctuations, and improvement of runoff water quality, as well as biodiversity and amenity values. Multiple benefits associated with urban ponds have only recently started to be appreciated, and examples of in-depth interdisciplinary insights remain rare. This paper gives an account of the ecosystem services provided by Blackford Pond, a semi-natural water body located within a nature reserve and nominated as a site globally important for scientific research. Despite elevated levels of polluting substances and eutrophication, the overall species richness of the site is high and the biodiversity of the locality is enhanced by the ecotone effect. The diversity of available plant hosts and substrates appears to benefit the fungal community and the abundance of aquatic invertebrate fauna appears to benefit the higher trophic levels. Hydrological modelling clearly shows that the pond increases the flood resilience of the surrounding area, despite not having been designed as a drainage feature. The application of the Natural Capital Planning Tool (NCPT) also reveals higher values (in relation to the values of amenity grassland) of such ecosystem services categories as biodiversity (+4.76 per hectare), aesthetic values (+4.67), flood risk regulation (+0.41), air quality (+0.28), local (+0.6) and global (+0.14) climate regulations. The discussion highlights a number of trade-offs among different ecosystem services (e.g. water quality vs. diatom research value, flood resilience vs. air quality and carbon capture, biodiversity of ectomycorrhizal vs. lichenised fungi), and considers which of the multiple benefits provided by the site may have not been fully reflected in NCPT calculations or the economic estimates obtained using contingent valuation (e.g. effects on hydrology, water quality, wildlife corridors, education and research value). The simultaneous consideration of biodiversity, hydrology, water chemistry and amenity, education, research and other values presented in this paper contributes towards a better understanding of the ecology and overall functioning of urban ponds, and helps to increase appreciation of their benefits and promote their public acceptability and further implementation. HIGHLIGHTS: Detailed insight is necessary to appreciate ecosystem services benefits. Among those, biodiversity, amenity value and flood resilience are the most important. Positive benefits also revealed for water quality and climate regulation. Overall species richness depends on the diversity of microhabitats and can be high despite problems with water quality. Ecological functioning is key for the understanding of ecosystem services. Graphical Abstract